The Influence of Pangkalan Sea Safety Operations of the Palembang Navy on Security Stability Bangka Strait Water - Danuasmoro, Wijoyo; Hendrawan, Arry (Jurnal Perikanan dan Kelautan, 2022)
The purpose of this study was to analyze how the influence of elemental readiness Opskamla, personnel ability and coordination with other stakeholders on the stability of the security of the waters of the Bangka Strait. This research method is a quantitative method with a population of military personnel Lanal Palembang and other stakeholders, then from the calculation with the Slovin formula it is obtained 40.12 rounded off to 40 samples. The data was then tested using linear regression method partially or simultaneously using SPSS 25 for Window Software. The results showed that there was a very strong, positive and significant influence both partially and simultaneously between the readiness of elements, the ability of personnel and coordination with other stakeholders on the stability of the security of the waters of the Bangka Strait.